Dynamics of Marriage Law Number 01 of 1974 concerning Age Limits for Marriage (Study in the Community of Lubuk Linggau City) - Solihin Solihin; Dwi Putra Jaya; M. Arafat Hermana (JURNAL HUKUM SEHASEN, 2022)
The objectives of this research are: a) To know the implementation of applying for a marriage dispensation in Lubuk Linggau City Community. b) To find out the factors that became the reason for the application for Marriage Despensation in Lubuk Linggau City Community. This research uses an empirical juridical approach. This approach aims to understand that the law is not merely a set of statutory rules that are normative in nature, but the law is understood as the behavior of people who are symptomatic in their lives, always interact and relate to social aspects, such as; economic, social and cultural aspects. The results of this study show; 1. The implementation of the application for dispensation for marriage is submitted by parents or guardians, through the stages and fulfilling the requirements determined by the Religious Courts, until following the trial until there is a decision by the Panel of Judges 2. Counting cases from 2018 to In 2020 there was an increase in the application for marriage dispensation, of which in 2018 there were 36 cases, in 2019 there were 43 cases and in 2020 there were 105 cases. The factors causing the increase in cases are pregnancy before marriage, weak religious education, cultural factors, economic factors, social media factors, fear of slander, changes in the age of marriage law. Of the many cases that were granted by the judge on the grounds that it would be avoided.